Penggunaan Teknik Mendongeng untuk Meningkatkan Keterampilan Berbicara pada Siswa SD Kelas Rendah - Rachmasisca, Frieska Maryova; Rohana, Rohana; Dedi, Fransisca S.O.; Prayogi, Riki (LPPM STKIP PGRI Bandar Lampung, 2025)
Speaking is one of the language skills that cannot be separated from everyday life, both in activities at home and at school. Speaking is one of the language skills that teachers must pay attention to so that students are able to express feelings or thoughts through language. For that, the right technique is needed to improve students' speaking skills. This research is a classroom action research (CAR). The purpose of this study is to improve the speaking skills of lower grade elementary school students by using good storytelling techniques. There are 2 cycles in this study. The subjects of this study were 28 lower grade students. Based on the results of the study, it was found that language learning using storytelling techniques can help students improve their speaking skills in lower grade elementary school students who are able to speak well in front of the class. There was an increase from cycle I to cycle II. In cycle I, 17 people achieved the KKM (60) or presented as 60.71%. While in cycle II, 27 people or 96.42% achieved the KKM.